De NAFLD a MAFLD para llegar a MASLD: La nueva nomenclatura de esteatosis hepática metabólica - Durán A., Daniel; Lizama R., Diego; Contreras M., Martina; Simian M., Daniela; Poniachik T., Jaime (Revista Hospital Clínico Universidad de Chile, 2025)
In 2023, the Delphi method was employed to revise the nomenclature for metabolic steatotic liver disease, resulting in the replacement of the term “metabolic dysfunction associated fatty liver disease (MAFLD)” with “metabolic dysfunction associated steatotic liver disease (MASLD)”. This modification has sparked concerns, criticism, and questions within the scientific community. This review investigates the evolution of terminology over recent decades, with a particular focus on the newly established diagnostic criteria. These criteria are more precise, mitigate the stigmatization associated with the disease, and offer improved alignment with its underlying pathophysiology. As such, this terminological refinement marks a significant advancement in the understanding of steatotic liver disease and presents new challenges for research and therapeutic development.